2012
DOI: 10.1073/pnas.1118665109
|View full text |Cite
|
Sign up to set email alerts
|

Surficial redistribution of fallout131iodine in a small temperate catchment

Abstract: Isotopes of iodine play significant environmental roles, including a limiting micronutrient ( 127 I), an acute radiotoxin ( 131 I), and a geochemical tracer ( 129 I). But the cycling of iodine through terrestrial ecosystems is poorly understood, due to its complex environmental chemistry and low natural abundance. To better understand iodine transport and fate in a terrestrial ecosystem, we traced fallout 131 iodine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 56 publications
2
25
0
Order By: Relevance
“…However, this is a minimum and approximate estimate as it assumes all leaf areas are projected orthogonal to rain direction and that no rain shadow is cast by nearby branches or tree crowns. By comparison, a full canopy cumulatively retains on the order of 40−90% of depositional flux as estimated either by the fraction of standing inventory found in vegetation 51,17,18 or from comparisons of precipitation Each unique accumulative atmospheric ratio history begins with the leaf-out date of the tree and is shown as a shaded 1-sigma confidence interval. For clarity, error bars on leaf symbols for oak (circle, ○) and for hemlock (square, □ ) depict larger 2-sigma propagated uncertainty.…”
Section: Quantitative Accumulation Of Atmosphericmentioning
confidence: 99%
“…However, this is a minimum and approximate estimate as it assumes all leaf areas are projected orthogonal to rain direction and that no rain shadow is cast by nearby branches or tree crowns. By comparison, a full canopy cumulatively retains on the order of 40−90% of depositional flux as estimated either by the fraction of standing inventory found in vegetation 51,17,18 or from comparisons of precipitation Each unique accumulative atmospheric ratio history begins with the leaf-out date of the tree and is shown as a shaded 1-sigma confidence interval. For clarity, error bars on leaf symbols for oak (circle, ○) and for hemlock (square, □ ) depict larger 2-sigma propagated uncertainty.…”
Section: Quantitative Accumulation Of Atmosphericmentioning
confidence: 99%
“…The transport and fate of radionuclide-tagged particles are controlled by the dynamics of fine-grained sediment transport in fluvial systems. Field observations have shown that finegrained sediment and atmospherically-deposited contaminants tend to accumulate in higher concentrations in channel margins that have been termed 'fine-grained channel margin' (FGCM) deposits (Skalak and Pizzuto, 2010;Landis et al, 2012a;Renshaw et al, 2013). However, the evolution of these deposits, such as the conditions under which they form and those under which they are eroded away, is not well established.…”
Section: Source Of Sedimentmentioning
confidence: 99%
“…The different sources of suspended sediment can be identified and quantified because of their different characteristic radionuclide activities. The activity of precipitation is expected to be greatest while sediment stored on the channel bed is expected to have a lower 7 Be activity than the channel margin deposits due to the relatively long (with respect to 7 Be's half-life) residence time on the streambed (Bonniwell et al, 1999;Landis et al, 2012a).…”
Section: Radionuclide Mass Balancementioning
confidence: 99%
See 1 more Smart Citation
“…Following the CNPP accident in 1986, the concentrations of fission products such as 131 I, 137 Cs, and 90 Sr in foodstuffs in Ukraine were more than 1,000 times the baseline fallout concentrations (Nesterenko et al 2010). As with observations of fallout, once these and other anthropogenic radionuclides were released into the environment, their activities steadily decreased owing to a combination of radioactive decay and biological and geochemical redistributions (e.g., Landis et al 2012).…”
Section: Radiological Doses To Humans and Societal Impactsmentioning
confidence: 99%